Leveraging meatpacking ownership concentration and community centrality to improve disease resiliency - Saitone, Tina L.; Schaefer, K. Aleks; Scheitrum, Daniel P. (Frontiers in Sustainable Food Systems, 2022)
The U.S. meat processing sector has been subject to ampli ed scrutiny after workers exhibited disproportionately high rates of COVID-19 infections and deaths. In re- sponse, Tyson Foods one of the largest meat packers in the country mandated that its employees be vaccinated against COVID-19 by November 1, 2021. In this paper, we investigate the impact that the Tyson vaccine mandate had on vaccine uptake, in- fection rates, and deaths in counties where Tyson processing facilities are located. We nd that the mandate resulted in approximately 35,000 additional vaccinations. The resultant vaccine uptake avoided 98 COVID-19 infections per day and nearly 75 COVID- 19-related deaths; the associated public health savings total 45.4 million. Employee health-related interventions at the corporate level can leverage industry ownership con- centration and the centrality of packing operations in host communities to improve health outcomes and disease resiliency well beyond the packing operations.